Heart failure morbidity and mortality: The impact of the SARS-CoV-2 pandemic in Northeast Brazil - Link , Caroline; Parlow , Jaqueline Meert; Sakakibara , Amy; Fonseca , Mariana; Karas , Bruna; Baroni , Gilbert; Mansani , Fabiana Postiglione; Sturzeneker , Mario Claudio Soares (Seven Editora, 2023)
Heart failure (HF) remains with a poor prognosis and high morbidity and mortality. The SARS-CoV-2 pandemic may have influenced these parameters due to the overload of health services, although regional characteristics may have had an influence. OBJECTIVE: To assess the impact of the SARS-CoV-2 pandemic on HF morbidity and mortality in Northeast Brazil through data analysis from DATA-SUS. METHOD: The average length of stay, the number of hospitalizations and deaths, and the mortality rate from 02/2017 to 11/2022 were evaluated, subdivided into pre-pandemic (02/2017 to 02/2020), pandemic (03/2020 to 06/2021), peak (12/2020 to 05/2021), the first and second trimester of the peak (12/2020 to 02/2021 and 03/2021 to 05/2021), mass vaccination (06/2021 to 12/2021) and year 2022 (01/2022 to 11/20222022). The subdivisions of the total evaluated period were compared with the others. The results were expressed in percentages. RESULTS: In the pre-pandemic, there was the highest monthly average of hospitalizations, with a reduction of 29% in the pandemic and 12% in the period of mass vaccination. There was a reduction in the monthly average of deaths in the pandemic period compared to the pre-pandemic period, with this average being similar in the mass vaccination and pre-pandemic periods. However, there was a significant increase in the mortality rate in the pandemic period (12.45%) when compared to the pre-pandemic period (10.9%), with the highest percentage observed in the mass vaccination period (12.79%). %). CONCLUSIONS: There were relevant consequences of the SARS-CoV-2 pandemic on HF morbidity and mortality in the Northeast region of Brazil, with a lower number of hospitalizations and increased mortality. During the vaccination period, the increase in hospitalizations and the higher mortality rate may reflect the difficulty in monitoring the disease in previous periods and greater access to health services. DOI:https://doi.org/10.56238/emerrelcovid19-008